Finding your calling: Matching skills with jobs in the mutual fund industry - Gjergji Cici; Mario Hendriock; Alexander Kempf (University of Cologne, Centre for Financial Research (CFR), 2022)
To best utilize labor, companies need to match employees' skills with jobs that best fit those skills. Exploiting unique features of the mutual fund industry, we identify instances when this matching happens for fund managers and study its consequences. After fund managers are matched, they improve their risk-adjusted performance significantly. Fund companies use this information to maximize company value by reallocating existing and directing new capital to their matched managers and by collecting higher fees from the matched managers' funds. In addition, they make the expertise of matched managers available to the other managers of the fund company.
Keywords: G23; J24; J62; M50; 330; human capital; mutual funds; occupational match finding